2021
DOI: 10.1016/j.clineuro.2021.106594
|View full text |Cite
|
Sign up to set email alerts
|

Microbleed patterns in critical illness and COVID-19

Abstract: Background Cerebral microbleeds are increasingly reported in critical ill patients with respiratory failure in need of mechanical ventilation and/or extracorporeal membrane oxygenation (ECMO). Typically, these critical illness-associated microbleeds involve the juxtacortical white matter and corpus callosum. Recently, this pattern was reported in patients with respiratory failure, suffering from COVID-19. Materials and methods In this retrospective single-center study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Of the 54 studies, 11 studies reported on ischemic strokes and 41 studies reported on ICHs. There were two case reports on mononeuritis multiplex (10,11), one case report on brachial plexopathy (12), three case reports on critical illness myopathy or neuropathy (12)(13)(14), five studies on cerebral microbleeds (12,(15)(16)(17)(18), and one case report of posterior reversible encephalopathy syndrome (18). Lastly, there were two studies that reported venous causes for neurovascular complications (19,20) and two studies that used electroencephalogram to investigate the electrophysiologic changes of patients with COVID-19 on ECMO (21,22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 54 studies, 11 studies reported on ischemic strokes and 41 studies reported on ICHs. There were two case reports on mononeuritis multiplex (10,11), one case report on brachial plexopathy (12), three case reports on critical illness myopathy or neuropathy (12)(13)(14), five studies on cerebral microbleeds (12,(15)(16)(17)(18), and one case report of posterior reversible encephalopathy syndrome (18). Lastly, there were two studies that reported venous causes for neurovascular complications (19,20) and two studies that used electroencephalogram to investigate the electrophysiologic changes of patients with COVID-19 on ECMO (21,22).…”
Section: Resultsmentioning
confidence: 99%
“…Characterized as small hypointense foci on gradient echo sequences or susceptibility weighted imaging, cerebral microbleeds associated with ECMO are typically found in the juxtacortical white matter and splenium of the corpus callosum. Three case reports and one case-control study noted cerebral microbleeds on MRI ( 12 , 15 – 17 ). There are several proposed mechanisms for ECMO-associated microbleeds, including hypoxia-induced microbleeds, gas emboli from ECMO, or infection-mediated microangiopathy.…”
Section: Discussionmentioning
confidence: 99%
“…This should be assumed according to the recent findings from the UK Biobank study, where COVID-19 patients had a significant loss of grey matter in the left parahypocampal gyrus, the left lateral orbitofrontal cortex and the left insula [ 33 ]. In addition to the gray matter decrease, COVID-19 critically ill patients also tend to have more incidence of microbleed at follow up [ 34 ], mainly found in the juxtacortical white matter, corpus callosum and internal capsule [ 35 , 36 ]. The implications of these structural and vascular alterations must be considered at the long term follow up of these patients, therefore cognitive and neurological evaluation should be carried out periodically.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of cerebral microbleeds is unknown but postulated to be multifactorial secondary to hypoxia, a proinflammatory state, hypercoagulability, disruption of endothelial cells and the blood brain barrier [2,6,7]. The presence of cerebral microbleeds and/or leukoencephalopathy remains associated with critical illness, worse functional outcome, increased hospitalization, increased morbidity and increased mortality in COVID-19 patients [3]. Earlier recognition of SARS-COV2 leukoencephalopathy and/or cerebral microbleeds could possibly modify and improve patient outcomes.…”
Section: Case Report #2mentioning
confidence: 99%